Overview of the Effectiveness of Aspirin, Ibuprofen, Acetaminophen On Teeth - Nikandish, Mehrasa; Alyari, Melika; Javaheri, Mohammadreza; Goderidze, Tamar (European Scientific Journal, ESJ, 2021)
The usage of medications like aspirin, ibuprofen and acetaminophen is well-accepted as pain relieving agents worldwide. Aspirin is a medication that is used not only for relieving pain but also for decreasing the risk of heart attack. Acetaminophen and ibuprofen have a significant role in decreasing chronic pain and inflammation. There is a deep connection between the dental procedures and the patients medicine intake. These effects can be known as side effects and damage the natural structure of the tooth or can be any disturbance in dental procedures especially in surgery and tooth extractions. Recognition of common medications and their effects is an important aspect not only for physicians but also for dentists and oral surgeons. The database of this article was derived from valid sources such as PubMed, Google scholar and Web of Science. The search method included the primary keywords like â€œaspirinâ€, â€œibuprofenâ€ and â€œacetaminophenâ€ combined with â€œteethâ€, â€œtooth extractionâ€, â€œoral cavityâ€, â€œdental procedures’’, and/or â€œbleeding timeâ€. Our results illustrated that a long-term application of aspirin favorably affects the patients who are suffering from angina, stroke or myocardial infarctions. Other findings confirmed that ibuprofen has antipyretic, analgesic and anti â€“ inflammatory features. Effective characteristics of paracetamol as the medicine of choice for the treatment of post-exodontia pain was demonstrated according to several studies. In this review article we provide details about the effects of the three aforementioned medications, their usage in the dental field and any adverse effects on healthy tooth structures.